The Effect of Health Education on Mother's Awareness about Child mental health - A. Elrahman, Ikhlass Mohammed; E. Elgai1i, Diaa (Gezira Journal of Health Sciences, 2021)
This is a prospective study which attempts to assess and raise the mothers awareness towards pre-school children psychological development in A1 Nasr Area in Medani City.  Fifty mothers were selected randomly and were subjected to a health education programme. Pre and post surveys and focus group discussions were conducted, so as to compare the level of mothers awareness before and after health education and training of mothers. A manual was developed to educate mothers about psychological development at pre-school age . Interpersonal communication with mothers through home visits, and distribuation of home care cards were major stratgies.   Six months later, following the base line and intervention phases, evalu- ation was conducted using the post survey and focus group discussions to the same group of mothers. The results indicated that there was an observable interest among moth-ers concerning the knowledge about the importance of mental health education as apart of the socialization process.